Desenvolvimento de queijo petit suisse caprino simbiótico sabor maracujá - Dantas, Tammyrys Maria de Oliveira (2019)
The use of goat milk in the formulation of its derivatives has been growing, growing in proteins of high biological value, essential fatty acids, vitamins and minerals. Affinity to add value to the dimensions of goat milk, probiotic and symbiotic dairy products to be developed, with a goal of enhancing the beneficial effects on health. The aim of this study was to develop and characterize the technological, physical, physicochemical, antioxidant, microbiological and sensory aspects of petit suisse consecutive cheeses of passion fruit, Lactobacillus mucosae CNPC007 and fructooligosaccharides. The quality of the probiotic bacterium and the fruitoligosaccharide that the quality of petit suisse cheese was terminal with 1, 14 and 28d days refrigerated refrigerated, considering the following treatment: QC (petit suisse - control cheese); QL, containing the probiotic microorganism Lactobacillus mucosae CNPC007; QF, composed of fructooligosaccharide (FOS) and QLF, containing a probiotic strain in association with FOS. All those who submit are tested and do not suffer synesters, presenting stability and retention in water. How the samples acidified during shelf life. In general, it is observed that the addition of the probiotic and / or FOS in the cheese production is not influenced on their physical and physical-chemical characteristics (p> 0.05), except for the moisture content along of refrigerated storage. The probiotic strain of Lactobacillus mucosae CNPC007 showed viability until the end of the guard life in the QL and QLF samples, with counts ranging from 8.76 to 11.57 and 11 CFU / g-1.35 to 10.24 log, respectively. In the process of flag of gastrointestinal, seen-of-effect monitoring of the matrix on the studied strain the largest when may associated with prebiotic (QLF), and other L. mucosae CNPC007 reached the ileum with 7.22 log CFU / g-1 counts. Regarding the phenolic benefit code, such as the QL and QLF samples, the higher levels compared to the others, being 85.15 and 92.76 mg / 100 g-1, respectively, were not used in their shelf life. Thus, when the preparation of a goat petit suisse is made, the preparation of passion fruit, Lactobacillus mucosae CNPC007 and / or fructooligosaccharides is presented as a product with functional potential, under which technologies, microbiological, nutritional and sensory can come to meet. the consumer market demand for functional dairy products.